Reflections on Local Knowledge and Institutionalized Resource Management: Differences, Dominance, Decentralization. - Feit, Harvey A. (GÉTIC, Universitè Laval, 1998)
In this paper I argue: a) that it is important to examine the differences between the uses of local knowledge in wildlife management as compared to its uses in economic botany and health professions; b) that the application of local knowledge by wildlife resource professionals is decisively shaped by the interests and conditions of state institutions; c) that the processes and structures linking state systems and local peoples are little influenced by the needs and well-being of local resource users; d) that we may nevertheless be at a historical moment in which this long-standing pattern is under increasing stress, as a result of global restructuring and government funding cuts, and in which the opportunities and benefits for change are significant for state and regional institutions, local users, and wildlife.
The author acknowledges constructive comments on earlier versions from: Michael Bravo, Gary Kofinas, Stuart Marks, Colin Scott, Frank Sejersen, and Joe Spaeder.
Keywords: Local Knowledge; Wildlife Management; Economic Botany; Patient-centered Health Care; Local Resource Management; Globalization; Political Economy; Decentralization